EMDR therapy for PTSD after motor vehicle accidents: meta-analytic evidence for specific treatment - Boccia, Maddalena; Piccardi, Laura; Cordellieri, Pierluigi; Guariglia, Cecilia; Giannini, Anna Maria (Frontiers in Human Neuroscience, 2015)
Motor vehicle accident (MVA) victims may suffer both acute and post-traumatic stress disorders (PTSD). With PTSD affecting social, interpersonal and occupational functioning, clinicians as well as the National Institute of Health are very interested in identifying the most effective psychological treatment to reduce PTSD. From research findings, eye movement desensitization and reprocessing (EMDR) therapy is considered as one of the effective treatment of PTSD. In this paper, we present the results of a meta-analysis of fMRI studies on PTSD after MVA through activation likelihood estimation. We found that PTSD following MVA is characterized by neural modifications in the anterior cingulate cortex (ACC), a cerebral structure involved in fear-conditioning mechanisms. Basing on previous findings in both humans and animals, which demonstrate that desensitization techniques and extinction protocols act on the limbic system, the effectiveness of EMDR and of cognitive behavioral therapies (CBT) may be related to the fact that during these therapies the ACC is stimulated by desensitization.